Therapeutic Dance Experimentation: Implementation of Post-Pandemic Movement Therapy - Dwiyasmono; Setya Widyawati; Supriyanto Supriyanto; Sriyadi Sriyadi; Sri Ningsih Sukirman (International Institute for Science, Technology and Education, 2023)
During the Covid-19 pandemic, people were constrained from carrying out physical activities due to social restrictions that had social, economic, and psychological impacts. People experience a decrease in body fitness, making them susceptible to disease. Dance therapy (DT) believes that the body and mind interact. Movements have a symbolic function and thus can help in understanding the self. Movement improvisation allowed people to experiment in new ways. Through non-verbal mediation, DT provided a method or channel for people to consciously understand the initial relationship with negative experiences, such as being affected by a pandemic. Through the unity of body, mind, and spirit, therapeutic dance provides a sense of wholeness to all individuals. DT enabled holistic creative expression by forming the whole person: mind, body, and spirit. The research aimed to apply a dance therapy model for children, disabilities, and older people to improve post-pandemic community fitness. This research supported the directives of the National Research Master Plan (NRMP) primarily on the health theme. It aligned with the ISI Surakarta Research Master Plan (RMP), focusing on developing art therapy. Method Development of the DT method went through four stages 1) Preparation: warm-up phase, a safe space was formed without obstacles or disturbances, and connections were formed that supported coparticipants' comfort in getting 2) Incubation: verbally encouraged participants to enter into the subconscious and develop an open attitude to create an atmosphere of serving participants, a relaxed atmosphere through dance movements. 3) Illumination: an integrated process through awareness with dialogue and self-reflection in which participants uncover subconscious motivations and increase self-awareness. 4) Evaluation: discussed the insights and significance of the DT process. This dance's creation applies the psychoanalysis theory by Sigmund Freud (1856-1939). We emphasized the behavioral aspects of human psychology by Sigmund Freud, which highlighted the realm of consciousness, which included three levels: the conscious, preconscious, and unconscious.